2007
DOI: 10.1007/s11627-007-9033-x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency somatic embryogenesis and regeneration in different genotypes of Sorghum bicolor (L.) Moench from immature inflorescence explants

Abstract: This study describes a protocol for the induction of high frequency somatic embryogenesis directly from immature inflorescence explants in three sorghum genotypes (SPV-462, SPV-839, and M35-1). The effect of various growth regulators on somatic embryogenesis was investigated. High frequency somatic embrogenesis was obtained on Murashige and Skoog (MS) medium supplemented with 2 mg l −1 2,4-dichlorophenoxyacetic acid (2,4-D), and addition of 0.5 mg l −1 kinetin (KN) in the medium further improved the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
5
16
0
1
Order By: Relevance
“…Immature inflorescences 1 cm in size were cut into 5 mm segments. The segments are numbered in order with the apical segment is segment 1 and the basal segment is segment 5. a Twenty-one days after initial platting on callus induction media b Ten weeks after initial platting on callus induction media c Forty-eight days after platting of callus onto regeneration media Same letters in a column are not significant at α=0.05 using the LSD test a Ten weeks after originally platting callus on callus induction media b Forty-eight days after transferring callus to regeneration media c Forty-eight days after transferring callus to regeneration media However 2,4-D was superior to dicamba for induction of embryogenic callus in pentaploid bermudagrass, sorghum, and millets (Kavi Kishor et al 1992;Rao et al 1995;Jain et al 2005;Jogeswar et al 2007). Seashore paspalum plants regenerated faster from dicamba-containing media and grew more vigorously when transferred to soil, similar to seashore paspalum plants grown from sod.…”
Section: Discussionmentioning
confidence: 99%
“…Immature inflorescences 1 cm in size were cut into 5 mm segments. The segments are numbered in order with the apical segment is segment 1 and the basal segment is segment 5. a Twenty-one days after initial platting on callus induction media b Ten weeks after initial platting on callus induction media c Forty-eight days after platting of callus onto regeneration media Same letters in a column are not significant at α=0.05 using the LSD test a Ten weeks after originally platting callus on callus induction media b Forty-eight days after transferring callus to regeneration media c Forty-eight days after transferring callus to regeneration media However 2,4-D was superior to dicamba for induction of embryogenic callus in pentaploid bermudagrass, sorghum, and millets (Kavi Kishor et al 1992;Rao et al 1995;Jain et al 2005;Jogeswar et al 2007). Seashore paspalum plants regenerated faster from dicamba-containing media and grew more vigorously when transferred to soil, similar to seashore paspalum plants grown from sod.…”
Section: Discussionmentioning
confidence: 99%
“…Casas et al (1993 reported that after DNA delivery, only three of eight genotypes produced embryogenic calli on selection medium, and only genotype P898012 regenerated plants under bialaphos selection. Genotype dependence was again demonstrated as the drawback for tissue culture in recent reports on sorghum regeneration (Maheswari et al 2010;Jogeswar et al 2007;Arulselvi and Krishnaveni 2009). Sorghum genotypes such as Tx430 and P898012 have been considered to be appropriate materials for regeneration and transformation, regardless of the fact that many sorghum genotypes have been screened and used in studies with this plant.…”
Section: Tissue Culture Barriermentioning
confidence: 95%
“…In sorghum, like most monocotyledonous plants, in vitro culture regimes are primarily somatic embryogenesis based systems (Elkonin and Pakhomova 2000;Jogeswar et al 2007; Kaeppler and Pedersen 1996;Pola et al 2008;Pola and Mani 2006;Sato et al 2004a). As per the second component of plant transformation, integration of genetic elements, sorghum has been successfully transformed using both direct DNA delivery methods (Battraw and Hall 1991) and Agrobacterium-mediated transformation protocols (Cai et al 2002;Gao et al 2005a, b;Gurel et al 2009;Howe et al 2006;Nguyen et al 2007;Zhao et al 2000).…”
Section: Sorghum Transformationmentioning
confidence: 99%